ARAB-MUSLIM PHILOSOPHY - Zh. O. Shaniyazov (Web of Journals Publishing, 2025)
The tradition of philosophical reflection, which arose and developed during the era of the dominance of the Islamic worldview in a predominantly Arabic-speaking civilization and has undergone a significant transformation in our days under the influence of Western civilization and philosophy.
Keywords: Philosophy, civilization, classical, Muslim, Western, term, history, medieval, Arabic-speaking, religion, society, traditions, problem, thought.